2021
DOI: 10.1002/ima.22621
|View full text |Cite
|
Sign up to set email alerts
|

TWEEC: Computer‐aided glaucoma diagnosis from retinal images using deep learning techniques

Abstract: A novel two-branched deep convolutional (TWEEC) network is developed for computer-aided glaucoma diagnosis. The TWEEC network is designed to simultaneously extract anatomical information related to the optic disc and surrounding blood vessels which are the retinal structures most affected by glaucoma progression. The spatial retinal images and wavelet approximation subbands are compared as inputs to the proposed network. TWEEC's performance is compared to three implemented convolutional networks, one of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 79 publications
(175 reference statements)
1
4
0
Order By: Relevance
“…Both these works showed that their deep learning methods outperformed various TL-based approaches from literature. These findings are in agreement with previous research that showed that in medical applications, a well-developed deep network can significantly outperform generic TL based methods [ 3 , 43 ].…”
Section: Literature Reviewsupporting
confidence: 93%
See 1 more Smart Citation
“…Both these works showed that their deep learning methods outperformed various TL-based approaches from literature. These findings are in agreement with previous research that showed that in medical applications, a well-developed deep network can significantly outperform generic TL based methods [ 3 , 43 ].…”
Section: Literature Reviewsupporting
confidence: 93%
“…Accordingly, the superiority of the proposed handcrafted L1-Contourlet features can be attributed to the relevance of the textural and statistical features computed from the different contourlet subbands. Deep pretrained networks commonly employed in medical applications are designed without consideration of the characteristics of the medical images or disease symptoms [ 3 , 43 ]. Features extracted by these generic deep networks might thus inefficiently represent the different classes resulting in less-than-optimal classification performance.…”
Section: Discussionmentioning
confidence: 99%
“…Shinde [18] captured the ROI of the input with the bright-spot approach and segmented by the U-Net for structural features. Recently, a two-branched DL network (TWEEC) is proposed by [19] for the classification of denoised retinal images in wavelet domain. In this study, both CNN branches were designed with similar architecture.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the size and geometry of the outer perimeter of the OD can be used to diagnose glaucoma. 3,4 Retinal vessels consist of venules and arterioles, which show up in retinal imaging as long, branched structures emerging from the OD. At least four billion people are estimated to suffer from vision impairment or blindness worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…For approximate macula and fovea detection, which is responsible for the keenest vision, the position and radius of the OD can be considered as references. Furthermore, the size and geometry of the outer perimeter of the OD can be used to diagnose glaucoma 3,4 . Retinal vessels consist of venules and arterioles, which show up in retinal imaging as long, branched structures emerging from the OD.…”
Section: Introductionmentioning
confidence: 99%